(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The question remains as to why the Catholic Church, with its moral authority and political influence, was unable to effectively oppose the implementation of reproductive health policies in a predominantly Catholic Philippines. Thus, this study examined the relationship dynamics of the Church and the state in the context of reproductive health policies in the country. Using the historical method, the data were mainly gathered from the Pastoral Letters issued by the Catholic Bishops Conference of the Philippines, the Official Gazette of the Republic of the Philippines and surveys conducted by opinion polling bodies. The collected data were then analyzed using historical approach and source criticism. The study revealed that the opposition of the Catholic Church to reproductive health policies has been always based on its teachings and doctrines on the dignity of the human person, the nature of marriage and purpose of sexual intercourse. Moreover, it also showed that political support and regime survival were important factors that determined the response of the government officials to Church criticisms and opposition to reproductive health policies. The wide public support for reproductive health policies and its successful implementation despite strong opposition from the Church implied that the stand of the Catholic Church on the issue failed to adapt to sociopolitical changes and respond to the changing needs of the Filipino people.